Exploring Teachers’ Perceptions of Integrating Multimodal Literacy into English Classrooms in Indonesian Primary Education - Dwi Jayanti, Erna; Damayanti, Ika Lestari (Universitas Nahdlatul Ulama Surabaya, 2023)
Multimodal literacy is seen as an integral part of 21st century learning since children are growing withvarious modes of communication in their daily life. Despite its significance emphasized in the nationalcurriculum, the study about multimodal literacy in English classrooms in Indonesia is still limited. Thisstudy aimed to expose the incorporation of multimodal literacy into English classrooms from the perspectiveof elementary and middle schools’ English teachers across Indonesia. This research was conducted throughan online questionnaire distributed through WhatsApp. There were sixty-one English teachers fromdifferent regions in Indonesia who volunteered to participate. A descriptive qualitative approach was usedto analyze the data to understand teachers’ perspectives and challenges of integrating multimodal literacy inEnglish classrooms. The study revealed that the majority of participants had the awareness of multimodalliteracy in the digital era. Moreover, they held positive attitudes towards the integration of multimodalliteracy in English classrooms even though there were limitations, such as the lack of school facilities,teachers’ understanding in effective strategies and teachers’ skills in using technologies. The teachersalso realized that multimodal literacy has been highlighted in the national curriculum, yet they havenot fully understood the concept of multimodal literacy. This study contributes to the understanding ofmultimodal literacy in English classrooms, that despite the positive attitudes and opportunities to integratemultimodal literacy in English classrooms, there is still a wide area for improvement. Thus, teachers’professional development should promote effective strategies to include multimodal literacy in Englishlanguage classrooms in response to the curriculum reform.